Digital Smile Design: Case Series - Mir, Hassam Anjum; Imran, Muhammad; Asif, Ali; Ahmed, Akhla Nadeem; Ayub, Muhammad Mansoor (Pakistan Armed Forces Medical Journal, 2022)
Aesthetic treatment is done to improve one’s appearance. Digital Smile Design, Computer-aided design and Computer-aided manufacturing (CADCAM) dentistry have revolutionized aesthetic dentistry. First, involving patients in treatment planning increases patient confidence and a happier outcome. Secondly, decreased appointments and decreased overall treatment time also facilitate patients in today’s busy lifestyle. However, this treatment method is uncommon in Pakistan due to a lack of knowledge and expensive equipment. This article aims to create awareness among the dentists so newer advanced treatment modality is adopted in Pakistan, bringing us at par with other countries.